2019
DOI: 10.1634/theoncologist.2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Delays and Barriers to Cancer Care in Low- and Middle-Income Countries: A Systematic Review

Abstract: Background. Advanced stage presentation of patients with is common in low-and middle-income countries (LMICs). A comprehensive analysis of existing delays and barriers in LMICs has not been previously reported. We conducted a systematic literature review to comprehensively outline delays and barriers to identify targets for future interventions and provide recommendations for future research in this field. Materials and Methods. Multiple electronic databases were searched using a standardized search strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
127
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 16 publications
(19 reference statements)
13
127
0
2
Order By: Relevance
“…Similar, a study performed in Malaysia revealed a median time interval of 5.5 months for the time between the first medical visit and diagnosis [30]. The present value of 56.0 days was within the median time span ranging from 0.9 to 5.0 months for the time interval between the first medical visit and the completed diagnosis of nine studies from low-and middle-income countries [31].…”
Section: Time Intervals and Delays In Tti Of All Patientssupporting
confidence: 86%
“…Similar, a study performed in Malaysia revealed a median time interval of 5.5 months for the time between the first medical visit and diagnosis [30]. The present value of 56.0 days was within the median time span ranging from 0.9 to 5.0 months for the time interval between the first medical visit and the completed diagnosis of nine studies from low-and middle-income countries [31].…”
Section: Time Intervals and Delays In Tti Of All Patientssupporting
confidence: 86%
“…Delay to cancer diagnosis can occur in any or all of three stages; presentation to the doctor (also called the patient interval), diagnosis, or access to treatment [ 13 ]. While diagnosis and treatment intervals were found to be comparable in low- and middle-income countries (LMICs) with those in high-income countries, the patient interval was found to be longer in LMICs [ 14 , 15 ]. A prolonged patient interval is a significant contributor to worse patient outcomes and a factor for 70% of global cancer mortality occurring in LMICs [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 6 While the incidence of cancers increases in LMICs, many cases continue to go undiagnosed because of a lack of high-quality population-based registries, and when diagnosed, the majority present at late-stage with consequently poor outcomes. 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…Breast and cervical cancer mortality and survival are largely influenced by the timeliness of diagnosis and effectiveness of treatment modalities. 7 8 10 In many LMICs, breast and cervical screening and early diagnosis programmes do exist in some form, however, they tend to be opportunistic and not well organised. 11–13 There is often poor access to high quality, affordable breast and cervical cancer treatment, particularly where the health systems are fragile or fragmented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation